Peran Kepala Madrasah dalam Pengembangan Kurikulum di MTs Negri 2 Sukoharjo: Penelitian - Musyaffa, Bima Ar Ramzi; Fauzan Rafiq N; Muhammad Thowas Al Y; Abdul Ghofur; Praptiningsih (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to analyze the role of the principal in curriculum development at MTs Negeri 2 Sukoharjo. The research employs a descriptive qualitative approach through in-depth interviews with the principal and teachers as the primary data sources. The findings reveal that the principal plays a central role as a strategic leader in translating the school’s vision and mission into curriculum policies. Curriculum development is carried out through the formation of a Curriculum Development Team consisting of school leaders, vice principals, and appointed teachers. The school implements curriculum diversification by offering several specialized programs such as Science Class, Tahfidz Class, International Class, KKO Class, and Regular Class, each with distinct competency focuses. The principal also ensures the quality of curriculum implementation through the Internal Quality Assurance System (SPMI) and the School Self-Evaluation (EDM). Meanwhile, teachers contribute by innovating learning strategies and developing technology-based teaching media, such as the SIMAKU digital platform. In conclusion, the effectiveness of curriculum development at MTs Negeri 2 Sukoharjo is strongly determined by the synergy between the principal’s leadership and the teachers’ creativity in implementing curriculum policies aligned with students’ needs and the Ministry of Religious Affairs’ directives.